Manajemen Risiko: Strategi Meningkatkan Keberlangsungan Bisnis UMKM - Putri, Dina Akmalia; Wulandari, Canda; Hasanah, Erika Rezky; Triayu, Putri Novia; Arsyadona, Arsyadona (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This research aims to find out how sustainable the business of micro, small and medium enterprises is. The research method used is a qualitative method. Based on the research results, it provides a theory about strategies to increase the sustainability of micro, small and medium business owners. Risk management is the key to the sustainability of MSMEe businesses. This research analyzes the importance of identifying, assessing and managing risks to reduce negative impacts on business. This study will also discuss various types of risks commonly faced by MSMEe as well as concrete steps in implementing risk management. By implementing effective risk management strategies, MSMEe can increase business resilience, make better decisions, and achieve long-term goals.